(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The present study was conducted to evaluate the mutagenic and antimutagenic potential of Cousinia thomsonii (CT) extract in bone marrow cells of male wistar rats using some important parameters like micronucleated polychromatic erythrocyte (MnPCE), mitotic index (MI), chromosomal aberrations (CA) and polychromatic erythrocyte to normochromatic erythrocyte ratio (PCE/NCE). 30 male rats of wistar strain were divided into 6 groups with 5 rats each group. Group 1 rats were taken as negative control having free access to distilled water and rat feed. Group 2 rats were taken as positive control treated with mutagen cyclophosphamide (CP) at dose of 60 mg/kg b wt. for 2 days. Group 3 and 4 were treated with CT extract at dose of 100 and 200 mg/kg b wt. for 20 days. Group 5 and 6 were treated with 100 and 200 mg/kg b wt of CT extract for first 18 days and for last 2 days with CP at dose concentration of 60 mg/kg. It was found that rats treated with CT extract alone did not produce any significant changes in MnPCE, PCE/NCE ratio, CA and MI when compared with control treated rats (group 1). However in group 5 and 6 rats treated with CT extract in combination with CP a protective effect was observed against the cyclophosphamide induced cellular mutagenicity. In concluding remark Cousinia thomsonii was found to show antigenotoxic potential and also produce protective antimutagenic effects against CP induced chromosomal damage.